Tamarindus indica increases the stability of jamu kunyit-asam herbal suspension over Citrus aurantifolia - wicaksono, arko jatmiko; Rakhmawati, rita; Wahyuningsih, Mae Sri Hartati; Syarif, Rul Afiyah; Prasetyo, Yacobus Christian (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
Rapid shelf-life of traditional supplementary drink still becomes major issue for herbal production in household industries. In this study the stability formula of an herbal suspension, so called as jamu kunyit-asam, was investigated. The jamu kunyit-asam Formula-1 (F1) contains combination of Citrus aurantifolia and Curcuma longa. While the Formula-2 (F2) is consisted by mixture of Tamarindus indica and C. longa. The two formulas were compared to justify better stability between preparations. No preservatives were added, in order to comply with the local regulation. To simulate the real situation, all samples were stored in 4 different conditions: opened bottle (room temperature), closed bottle (room temperature), closed bottle (refrigerator), and freeze-thaw condition. To evaluate the stability profile, an organoleptic testing and pH alteration were frequently checked for 12 consecutive days. Several parameters including color changing, sting odor, and microscopic appearance were looked over. As the results, mold, precipitation and pungent odor were formed faster from the F1 (C. aurantifolia combined with C. longa). These findings indicates that jamu kunyit-asam herbal drink suspensions containing C. longa has less stability in combination with the C. aurantifolia (F1) compared to the T. indica (F2).